O autor segundo ele mesmo: a escrita de si em Cadernos de Lanzarote, de José Saramago - Fernandes, Fernanda Buzzon [UNESP] (2015)
The dissertation analyzes the thematic and formal transgressions undertaken by Portuguese writer José Saramago, in the works Cadernos de Lanzarote (1998a) and Cadernos de Lanzarote II (1999), in relation to the diary, especially in its inauthentic mode, featured by a less spontaneous construction, because of the publication - disclosure to many readers completely different from the diarist - that changes it formal and thematically, and in reference to the dialogue with the audience. The first chapter is about the genealogy of the diary. The second is devoted to critical appreciation of Cadernos de Lanzarote. Generic transgressions, the authorship voices are considered in the third chapter. The purpose of this paper is to discuss how, as opposed to traditional journals, the self-referential work of Portuguese writer is public, not private, with particular characteristics regarding gender paradigms. To achieve this purpose, the dissertation seeks to provide a more detailed theoretical presentation of the diary, contemplating it from its origin - there were about 3,000 BC, concomitantly with the invention of writing - until nowadays, when it occurs the revolution brought by Web 2.0 I the self-referential writing